(untitled) (GYMNASIUM, 2014)
The growth and development of the human body, being influenced by endogenous and exogenous factors, but more so in childhood and youth, conditions the development of the human beings throughout their lives, prefiguring a favorable or an unfavorable direction of their general ability to adapt to the daily demands. This study has been conducted under the consideration that the assessment of certain morpho-functional parameters in middle school children, and especially their correlation, can offer information whether the growth and development process takes place within normal limits, or presents certain deviations. The results of the study highlight the fact that certain parameters correlate more, while others, less, but the general conclusion leads us to the idea that the insufficient training of children in variated physical effort, and the existence of certain deviations from the right alignment of the body, negatively influence the process of growth and development in middle school pupils. The results can be used for intensifying the efforts to ensure the necessary conditions so that the growth and development of middle school pupils would take place under optimal parameters.